2000
DOI: 10.1038/sj.bmt.1702162
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric marrow transplantation for acute leukemia using unrelated donors and T-replete or -depleted grafts: a case-matched analysis

Abstract: Summary:A retrospective, case-matched analysis of the short-term toxicity, risk of GVHD and relapse as well as outcome in pediatric unrelated marrow transplantation was conducted by comparing recipients of T-replete and -depleted grafts in a two-center setting. Both groups contained 30 patients with acute leukemia matched by age at transplant, gender, primary diagnosis and disease status. Acute (90% vs 53%) and chronic (48% vs 0%) GVHD were more common among recipients of Treplete grafts. No significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…This assumption is supported by previous studies reporting a higher incidence of leukemia relapse using Campath-1G in the conditioning regimen and T cell-depleted grafts. 8,9 Our data on the favorable outcome of two patients with high-level MRD before transplantation with unmanipulated grafts are supported by a recent report from Uzunel et al, 10 who show that less than 50% of patients transplanted with unmanipulated grafts do not relapse despite the presence of residual disease before BMT. Furthermore their study demonstrates a strong correlation between the occurrence of acute and chronic GVHD and sustained remission.…”
Section: Discussionsupporting
confidence: 71%
“…This assumption is supported by previous studies reporting a higher incidence of leukemia relapse using Campath-1G in the conditioning regimen and T cell-depleted grafts. 8,9 Our data on the favorable outcome of two patients with high-level MRD before transplantation with unmanipulated grafts are supported by a recent report from Uzunel et al, 10 who show that less than 50% of patients transplanted with unmanipulated grafts do not relapse despite the presence of residual disease before BMT. Furthermore their study demonstrates a strong correlation between the occurrence of acute and chronic GVHD and sustained remission.…”
Section: Discussionsupporting
confidence: 71%
“…9 GVHD was responsible for only 5% of deaths in our series, in contrast to studies with T-replete URD BMT in which grades III-IV acute GVHD occur in up to 45% of serologically matched recipients. 3,14,15 TCD has been reported to increase the risk of leukemic relapse, and the UK Campath study for ALL noted a relapse rate of 67%. 4 However, our relapse rate was 6% for ALL patients, and 23% for the AML/MDS patients, which is comparable to studies of T-replete URD BMT for pediatric leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…However, these alternative donor transplants are associated with increased graft-versus-host disease (GVHD), graft rejection, and slow immune reconstitution. [1][2][3] T-cell depletion (TCD) may decrease the risk of GVHD, but some studies have shown an increased risk of rejection and relapse due to the loss of the graft vs. leukemia effect. 4,5 Partial (TCD) may decrease the risk of GVHD, yet allow for engraftment and retention of a graftvs-leukemia effect.…”
mentioning
confidence: 99%
“…18 The probability of relapse may be decreased by using T-replete transplants at the expense of more acute and chronic graft-versus-host disease (GVHD) and a higher TRM. 19 On the other hand, relapse after allograft remains problematic as the chance of response to donor lymphocyte infusion (DLI) is very low (at 18 and 5% in the two largest published series 20,21 ) and usually is not durable. The possibility of using pre-emptive DLI in those subjects at high risk of relapse has been investigated in children and it may be possible to apply these techniques to adults.…”
Section: Specific Indications For Ud Hsct In Adult Allmentioning
confidence: 99%